Effects of cascading failure intervals on synchronous stability. (March 2019) - Li, Chenhao; Xue, Yusheng
Highlights: A stability analysis method is proposed in consideration of fault intervals. The proposed method chooses the most unstable interval. The method captures the periodicity of stable margin variations with intervals. The mechanism of the periodicity is analyzed in consideration of time-varying factors. The proposed method is compared with common assumptions in cascading failure TSA. Abstract: Cascading failure analyses are mainly based on simultaneous or quasi-steady-state (QSS) assumptions, which are inappropriate in cases of rapid cascading failure analysis and control. Fault interval is considered in the stability analysis of cascading failure for the first time in this article. Based on the extended equal area criterion (EEAC), a transient stability analysis method is proposed for cascading failure in consideration of intervals. The results show the periodicity of stable margin variations with intervals. The conclusions are validated in a Hamiltonian system, and the effects of time-varying factors are analyzed. The OMIB case shows that it may be over-optimistic to assess stability levels under simultaneous or QSS assumptions. The validity of all conclusions in this paper is verified with the New England system and with an actual power system.